OP0224 Anti-AT1R and Anti-ETAR Autoantibodies from Patients with SSC and their Agonistic Effects. (23rd January 2014) - Kill, A.; Günther, J.; Becker, M. O.; Dragun, D.; Burmester, G.-R.; Riemekasten, G.
Abstract : Background: Autoantibodies reactive to angiotensin II type 1 receptor (AT1 R) and endothelin 1 type A receptor (ETA R), anti-AT1 R and anti-ETA R autoantibodies, are found in patients with Systemic sclerosis (SSc) as a prototypic connective tissue disease with limited therapeutic options. SSc is characterized by three major hallmarks: autoimmunity, vasculopathy and fibrosis. Anti-AT1 R and anti-ETA R autoantibodies (Ab) have been demonstrated in association with clinical symptoms of SSc including vascular and fibrotic complications. Therefore, direct agonistic effects of anti-AT1 R and anti-ETA R Ab were studied. Objectives: To analyse anti-AT1 R and anti-ETA R Ab-mediated agonistic effects in in vitro and in vivo experimental settings. Methods: Human microdermal endothelial cells-1 (HMEC-1) were treated with IgG from SSc patients positive for anti-AT1 R and anti-ETA R Ab, or with IgG of healthy donors (NC-IgG). To demonstrate angiotensin- and/or endothelin-receptor activation, cells were pre-treated with specific receptor inhibitors, either alone or in combination. Cell activation was measured by IL-8 chemokine expression, adhesion molecule VCAM-1 expression, trans-endothelial neutrophil migration and ROS activation using qRT-PCR, sandwich ELISA, cell culture inserts and fluorescence analysis. In vivo effects were measured by autoantibody transfer into healthy C57Bl/6J mice and analysis of cellular BALF composition. Results: Upon treatment with anti-AT1 R and anti-ETA R Ab positive SSc-IgG, HMEC-1 cells increased IL-8 mRNA levels and IL-8 protein secretion into culture supernatants compared to cells treated with NC-IgG. Levels of IL-8 mRNA and protein were decreased in samples that were pre-treated with specific angiotensin- and endothelin-receptor blockers. Culture supernatants with increased IL-8 protein levels due to SSc-IgG treatment, showed an increased potential to recruit neutrophils through an endothelial cell layer, compared to supernatants of NC-IgG treated samples. Again, specific angiotensin- and endothelin-receptor inhibition showed a reduction in neutrophil recruitment. Culture supernatants conditioned with SSc-IgG increased reactive oxygen species (ROS) production in healthy donor neutrophils compared to supernatants with control treatment. Furthermore, HMEC-1 cells showed also increased mRNA levels of VCAM-1 with significant reduction by receptor inhibition. Moreover, mice that received anti-AT1 R and anti-ETA R Ab positive SSc-IgG showed significantly increased neutrophil number in BALF compared to NC-IgG. Conclusions: Our findings demonstrate the potential of anti-AT1 R and anti-ETA R Ab to induce pathogenic effects in vitro and in vivo . Activation of endothelial cells by anti-AT1 R and anti-ETA R Ab might reflect in some aspects the situation as seen in vivo and could thereby be an important factor in disease pathogenesis. Furthermore, cell activation by these autoantibodies induced neutrophil recruitment in vitro. Finally, activation of neutrophil recruitment by anti-AT1 R and anti-ETA R Ab positive SSc-IgG, demonstrated the potential to directly induce pathogenic effects in healthy mice in vivo . Thus, angiotensin- and endothelin-receptor activation by anti-AT1 R and anti-ETA R Ab could significantly contribute to pathogenesis of SSc. Disclosure of Interest: None Declared